2020
DOI: 10.1177/1525740120902993
|View full text |Cite
|
Sign up to set email alerts
|

Using Qualitative Methodologies in Speech-Language Pathology: An Example From Serving Students With Hearing Loss

Abstract: This article demonstrates the use of qualitative methodologies to provide a description of an intervention framework and goals for students with hearing loss in general education. Because of advances in technology, the majority of students with hearing loss are now educated in general education classrooms. Many of these students are not eligible for special education services although their hearing loss does compromise their functioning in many areas of daily life. This investigation employed two qualitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Participants with disabilities described the complex interactions between their disability and mental health, which represented important considerations in their professional life (Hudock et al, 2018;Westby, 2021). Lastly, clinicians with linguistic and ethnic minority backgrounds often used an intersectional lens to express their experiences (Lowell et al, 2018).…”
Section: Subjectmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants with disabilities described the complex interactions between their disability and mental health, which represented important considerations in their professional life (Hudock et al, 2018;Westby, 2021). Lastly, clinicians with linguistic and ethnic minority backgrounds often used an intersectional lens to express their experiences (Lowell et al, 2018).…”
Section: Subjectmentioning
confidence: 99%
“…The past experiences of underrepresented SLPs could play a significant role in their decision to become SLPs. For example, participants with disabilities described how having had exposure to SLP as clients facilitated their decision to seek a career in this field (Hudock et al, 2018;Westby, 2021). Participants with linguistic and ethnic minority backgrounds were motivated to join the profession to give back to their community and support them achieve a better future (Lowell et al, 2018).…”
Section: Subjectmentioning
confidence: 99%
See 2 more Smart Citations
“…I recently published a qualitative study that reported the experiences of EM, a speech-language pathologist (SLP) with a severe bilateral hearing impairment who developed an educational program for students with hearing loss (HL) based on what she wished she had had as a student (Westby, 2020). I used the biographical narrative interpretive method (BNIM) when interviewing EM.…”
mentioning
confidence: 99%